Study of High Sensitive C-Reactive Protein in Ischemic Heart Disease - Ferdous, BA; Sultana, N; Ahmed, S; Khan, EH; Atia, F; Sultana, S; Shahnaj, A (Bangladesh Journal of Medical Biochemistry, 2013)
C-reactive protein (CRP) is a sensitive marker of inflammation, and elevated levels have been associated with future risk of myocardial infarction (MI). Even elevated CRP in healthy men and women can predict the future coronary events. This cross-sectional analytical study was undertaken to observe association between high hsCRP level with chronic ischaemic heart disease and was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2010 to June 2011. A total 50 cases were selected purposively according to the selection criteria form the patients admitted in the Department of Cardiology, Dhaka Medical College Hospital with chronic ischaemic heart disease (IHD). Diagnosed IHD patients were taken as cases; age- and sex-matched 50 healthy subjects were taken as controls. Serum hsCRP and serum TC, TAG, LDL-C and HDL-C were measured in all study subjects. The mean serum hsCRP concentration in cases and controls were 11.22±7.64 mg/dl and 1.72±0.98 mg/dl respectively. Serum hsCRP, Total Cholesterol, TAG and LDL-C were significantly higher in cases than control subjects. Serum HDL-C was significantly lower in cases than control subjects. The present study reveals that the patients of chronic ischemic heart disease have been found to have close association of increased level of hsCRP. DOI: http://dx.doi.org/10.3329/bjmb.v6i1.13281 Bangladesh J Med Biochem 2013; 6(1): 11-13